A prayer for the night [large type] - Gaus, Paul L. (Gaus, Paul L. Amish-country mystery., 2011)
"Sara Yoder is learning that danger can lurk in freedom's shadow. John Schlabaugh and Abe Yoder - Sara's friends and fellow travelers on the Amish rite of passage, Rumschpringe - are missing. Worried, but distrustful of most English, Sara calls Pastor Cal Troyer for help. Then Sara also disappears. Troyer, along with his old friends Professor Michael Branden and Sheriff Bruce Robertson, must race against the clock to find a murderer and break a ruthless drug ring operating within the heart of Ohio's Amish country" -- Cover verso.